Halal dalam Konsepsi Alquran dan Penerapannya pada Industri Ikan Salai Patin Desa Wisata Kampung Patin Koto Masjid Kabupaten Kampar - Gani, Erman; Rahman, Syahrul; Ajidin, Zilal Afwa; Zulirfan, Navri; Nabila, Sally; Ismardi, Ismardi (MUI Kota Pekanbaru, 2023)
This article seeks to explore the application of the halal industry in the production of Salai Patin fish in the Kampung Patin Koto Masjid Tourism village, Kampar Regency. Many factors can influence the successful implementation of the halal industry, including understanding the concept of halal, the urgent need to develop the Islamic economy, and the profile of Kampung Patin Tourism Village as the center of Patin Fish production. The process of implementing the halal industry begins with awareness and training. Ensuring that catfish business actors understand the sharia principles underlying halal products. Halal certification is an important step to convince consumers that Salai Patin fish products meet the standards of purity and halalness. Collaboration with halal certification bodies and authorized government agencies is also a key factor in maintaining product integrity and quality. The prospect of the halal industry promises sustainable economic growth in Kampung Patin Tourism Village, with the expectation that salai patin fish products can present wider business opportunities, both in local and international markets. This development will support the increasingly globalized idea of sharia economy, changing people's perception of Islam as a religion that is rahmatan lil alamin.